2015
DOI: 10.1371/journal.pone.0130395
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin D Regulates Cytokine Patterns Secreted by Dendritic Cells to Promote Differentiation of IL-22-Producing T Cells

Abstract: One central mechanism, by which vitamin D regulates human immune responses, is the direct modulation of dendritic cells (DCs). However, the effect of vitamin D on several key DC functions, such as the secretion of central inflammatory cytokines, remains controversial. Moreover, whether vitamin D treatment of DCs regulates their ability to promote differentiation of IL-17-/IL-22-producing T cell subsets, such as Th17 and Th22 cell, is not known. Here, we report that vitamin D treatment during differentiation of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
41
1
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 47 publications
(46 citation statements)
references
References 84 publications
3
41
1
1
Order By: Relevance
“…This was associated with a global attenuation of LPSinduced transcriptional responses. We could not replicate a previous report that pro-inflammatory innate immune responses were augmented by vitamin D. 14 The inhibitory effects of in vitro vitamin D treatment on innate immune signalling was reproduced in primary peripheral blood myeloid DC, but not in monocytes within the same PBMC samples or in MDM. In fact, we observed increased innate immune activation of both NF-jB and MAPK pathways in monocytes within PBMC following in vitro incubation with vitamin D. At face value, this observation also contrasts with a previous report that in vitro incubation of monocytes with vitamin D does inhibit innate immune signalling and transcriptional responses, possibly as a result of down-regulated expression of innate immune receptors such as TLR2 and TLR4.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…This was associated with a global attenuation of LPSinduced transcriptional responses. We could not replicate a previous report that pro-inflammatory innate immune responses were augmented by vitamin D. 14 The inhibitory effects of in vitro vitamin D treatment on innate immune signalling was reproduced in primary peripheral blood myeloid DC, but not in monocytes within the same PBMC samples or in MDM. In fact, we observed increased innate immune activation of both NF-jB and MAPK pathways in monocytes within PBMC following in vitro incubation with vitamin D. At face value, this observation also contrasts with a previous report that in vitro incubation of monocytes with vitamin D does inhibit innate immune signalling and transcriptional responses, possibly as a result of down-regulated expression of innate immune receptors such as TLR2 and TLR4.…”
Section: Discussioncontrasting
confidence: 99%
“…7 Counterintuitively, a recent report suggests that vitamin D preconditioning enhanced the expression of canonical pro-inflammatory cytokines, such as TNF-a, IL-1b and IL-6 following innate immune stimulation of MDDC with LPS for 4 hr. 14 We observed that MDDC differentiation in the presence of 1,25[OH]D down-regulated basal level expression of TNF-a selectively, but transcription of all three cytokines was robustly up-regulated in response to LPS stimulation. The only significant difference attributable to vitamin D was modest attenuation of IL-6 transcriptional up-regulation ( Fig.…”
Section: Vitamin D Inhibition Of Innate Immune Responses In Mddcmentioning
confidence: 81%
“…The actions of vitamin D are complex and affect both innate and adaptive immune systems to reduce inflammation, promote immune tolerance, and enhance antimicrobial responses. Specifically, vitamin D induces antimicrobial peptide synthesis (93), triggers the expression of inducible nitric oxide synthase (67), represses the expression of Toll-like receptors (TLRs) (48), and inhibits the production of proinflammatory cytokines by innate immune cells (77). In addition, vitamin D receptor activation inhibits dendritic cell differentiation and maturation, as shown by decreased maturation-induced surface markers.…”
Section: Inflammation: Bone and Mineral Metabolismmentioning
confidence: 99%
“…[17] Vitamin D plays a key role in modulating the secretion of cytokines. [18] Vitamin D may modulate the association of depression and in ammation via its role in the immune system. [19,20] There are several limitations in this study.…”
Section: Discussionmentioning
confidence: 99%